A study of cervical Papanicolaou smears examination in patients with abnormal vaginal discharge - Patel, Komal; Hathila, R. N.; Chaudhri, Pallavi; Patel, Siddhi M. (International Journal of Research in Medical Sciences, 2019)
Background: Reproductive tract infection represents major public health problem in developing countries. Cervical infections are common problems among women of reproductive age and associated with clinical complaints of vaginal discharge. Pap smear is a screening test to diagnose various abnormal pathology of cervix. Aims and objectives of this study was to identify various causes of vaginal discharge and frequency of various pathogenic microorganisms in cervical smear. Methods: This was hospital based descriptive study carried out on 300 female patients who attended obstetrics and gynecology clinic at tertiary care hospital with compliant of vaginal discharge. Cervical smear samples were collected, conventional smears were prepared by trained technical staff and stained using Papanicolaou (Pap) technique. Results: The most common age group affected with vaginal discharge was 26 to 35 years with 115 cases. The most common associated symptom was lower abdominal pain seen in 75 cases. Most frequent findings on per speculum examination was thick whitish discharge in 186 cases and the most common pathogenic organism found was Bacterial Vaginosis (BV) in 177 cases. Conclusions: The study emphasizes the need for educating women of rural community to raise the awareness for cervical Pap screening.